A Rare Presentation of Autonomously Functioning Papillary Thyroid Cancer: Malignancy in Marine-Lenhart Syndrome Nodule - Mehmet Uludag; Nurcihan Aygun; Alper Ozel; Feyza Yener Ozturk; Rabia Karasu; Banu Yilmaz Ozguven; Bulent Citgez; Mehmet Mihmanli; Adnan Isgor (Case Reports in Surgery)
Objective. Marine-Lenhart Syndrome (MLS) is defined as concomitant occurrence of autonomously functioning thyroid nodule (AFTN) with Graves’ disease (GD). Malignancy in a functional nodule is rare. We aimed to present an extremely rare case of papillary thyroid cancer in a MLS nodule with lateral lymph node metastases. Case. A 43-year-old male presented with hyperthyroidism and Graves’ ophthalmopathy. On Tc99m pertechnetate scintigraphy, a hyperactive nodule in the left upper thyroid pole was detected and the remaining tissue showed a mildly increased uptake. The ultrasonography demonstrated 15.5 × 13.5 × 12 mm sized hypoechoic nodule in the left upper pole of the thyroid and round lymph nodes on the left side of the neck. Fine needle aspiration biopsy (FNAB) of the nodule and lymph node revealed cytological findings consistent with papillary cancer. Total thyroidectomy with central and left modified radical neck dissection was performed. On pathologic examination, two foci of micropapillary cancer were detected. The skip metastases were present in three lymph nodes on the neck. Conclusion. AFTN can be seen rarely in association with GD. It is not possible to exclude malignancy due to the clinical and imaging findings. In the presence of suspicious clinical and sonographic features, FNAB should be performed.